Pengaruh Pelayanan Prima Dan Kualitas Produk Terhadap Kepuasan Pelanggan Di Eden Daily International Food Semarang - Julian Andriani Putri; Ninuk Subandyah; Henry Yuliamir; Dyah Palupiningtyas; enik rahayu (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2022)
Food will certainly please its customers. Retaining customers is generally more profitable than changing customers, because the cost of acquiring a new customer can be many times the cost of retaining an existing customer. This study aims to analyze the effect of service quality and product quality on customer satisfaction at the Spoon Bebek Restaurant in Semarang. The population is all consumers at the Spoon Duck Restaurant with a total sample of 100 respondents. The research analysis tool uses multiple linear regression where the validity and reliability tests were previously carried out. The test results are proven. The results showed that there was a positive and significant influence on service quality on customer satisfaction at the spoon duck restaurant in Semarang (t count = 4,520 and p < 0.05). Meanwhile, the results of other studies indicate that there is a positive and significant effect on the quality of food products on consumer satisfaction at the spoon duck restaurant in Semarang (t count = 6.123 and p <0.05).